Do memory concerns and self-efficacy predict academic performance in undergraduate students with memorization practice? - Pilotti, Maura; Alzahid, Dana; Faisal, Nouf; Waked, Arifi; El-Moussa, Omar J. (Frontiers in Psychology, 2025)
IntroductionThe main aim of the present study was to examine the extent to which self-reported prospective and retrospective memory concerns and academic self-efficacy predict academic attainment in sophomore and junior undergraduate students.MethodSubjective memory and self-efficacy reports were completed by a convenience sample of an understudied population of bilingual Saudi Arabian female students with a verbatim memory educational past. They were enrolled in a self-assessment course.ResultsResponses illustrated greater prospective than retrospective memory concerns. A modest relationship between memory concerns and academic self-efficacy was also found, suggesting that memory issues play a minor role in the confidence students possess in their academic abilities. Academic attainment was minimally related to academic self-efficacy and not at all to self-reported prospective or retrospective memory difficulties.DiscussionThese findings illustrate that awareness of memory failures does not correspond to an inability to satisfy academic demands, since it may bring about the use of compensatory strategies. Implications for teaching and learning are discussed.